SMART UNIVERSITIES: GLOBAL TRENDS IN ARTIFICIAL INTELLIGENCE AND EDUCATION 4.0 - Vélez, Wilson Alexander Zambrano; Delgado-Cobeña, Elan Ignacio; Molina-Santana, Cinthya Lisbeth; Macías-Loor, Jorge Sebastián; Vera, Kevin Andree Mendoza (Veredas do Direito, 2026)
The integration of artificial intelligence into higher education has driven the consolidation of the smart university paradigm within the framework of Education 4.0, promoting the digital transformation of university ecosystems. However, despite the accelerated growth of scientific output in this field, existing research exhibits marked thematic fragmentation and uneven regional distribution. The objective of this study was to analyze global research trends on artificial intelligence and Education 4.0 in the context of smart universities using a bibliometric approach. To this end, a descriptive and exploratory bibliometric analysis was conducted on peer-reviewed scientific articles indexed in the Scopus database during the period 2020–2025, following the guidelines of the PRISMA 2020 statement. The data were processed using the Bibliometrix (R) and VOSviewer tools, considering indicators of scientific productivity, impact, and keyword co-occurrence. The results show sustained growth in publications, high author dispersion, and a geographical concentration of production, primarily led by countries in Asia and the Middle East. Artificial intelligence is consolidating its position as a driving force, closely linked to Education 4.0, engineering training, and emerging technologies such as blockchain and educational chatbots, reflecting a transition toward more integrated and intelligent university ecosystems. In conclusion, the findings confirm that research on smart universities is in a phase of expansion and thematic diversification, highlighting the need to strengthen integrative theoretical frameworks and foster greater participation from underrepresented regions, particularly Latin America, to guide digital transformation strategies in higher education.